LEARNING MANAGEMENT SYSTEM IN EDUCATION: IMPLICATION FOR UNDERGRADUATE'S ATTITUDES AND MOTIVATION - ONU, ANN E (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Attitudes and motivation are essential components of the educational ecosystem of every society. The constructs are among the primary determinants of success in education. Past research has underscored the varying significance of digital innovations in developing teaching and learning in Nigeria. However, little is known about the learning management system's impact on student attitudes and motivation. The present study examined the effect of digital learning on students' learning motivation and attitude. A cross-sectional design was adopted, and one hundred and twenty-seven (n=127) students conveniently pooled from public tertiary institutions in Enugu State, Nigeria, participated in the study. The respondents completed a self-report measure of digital learning, learning motivation, and attitude. The result of the linear regression model showed that LMS resources significantly predicted attitudes and motivation in undergraduates. The study concludes that LMS platforms are indispensable in promoting learning enthusiasm.